Two-dimensional (2D) fabrics and three-dimensional (3D) preforms for ballistic and stabbing protection: A review. Issue 18 (November 2017) - Bilisik, Kadir
In this study, the impact resistance of two-dimensional (2D) fabrics and three-dimensional (3D) preforms is explained. These fabrics and preforms include 2D and 3D woven and knitted flat and circular fabrics. Various types of soft/layered structures as well as rigid composite are outlined with some design examples for ballistic and stab threats. The recent developments in nanotubes/nanofibers and shear-thickening fluids (STF) for ballistic fabrics are reviewed. The ballistic properties of single- and multi-layered fabrics are discussed. Their impact mechanism is explained for both soft vest and rigid armor applications. Analytical modeling and computational techniques for the estimation of ballistic properties are outlined. It is concluded that the ballistic/stab properties of fiber-reinforced soft and rigid composites can be enhanced by using high-strength fibers and tough matrices as well as specialized nanomaterials. Ballistic/stab resistance properties were also improved by the development of special fabric architectures. All these design factors are of primary importance for achieving flexible and lightweight ballistic structures with a high ballistic limit.